Survey, Characterization and Mapping of Ground Water Quality and its Effect on Soil Properties in Gurugram Block in Haryana - Bhatia, Rishav; Yadav, Parmod Kumar; Kumar, Sawan; Ramprakash; Kumar, Satender; Jat, Mukesh Kumar (Journal of Soil Salinity and Water Quality, 2023)
In Gurugram block of Gurugram district, a survey was conducted to evaluate the quality of the groundwater and determine how it affected the soil qualities. Using a handheld GPS, 72 groundwater samples and 40 soil samples overall were taken at two sites, four depths each, in the Gurugram block of the district. The pH, EC, SAR and RSC of ground water ranged from 7.38 - 8.03, 0.75-5.58 (dS m-1), 4.44 - 21.75 (mmol l-1)1/2 and nil to 4.50 (me l-1), respectively. The anion contents followed the pattern Cl− > SO42− > HCO3− > NO3− > CO32− whereas the cations were found to be in the following order: Na+> Mg2+> Ca2+> K+. The village Sehrawan had the lowest saturation rate (28.84%) and the village Kherki Majra had the highest saturation percentage (34.57%). The settlement of Gurugram Rural (1.22 dS m-1) in the Gurugram block has the lowest EC of saturated extract. The Hamirpur village had the highest EC of saturated extract (6.12 dS m-1) whereas Hamirpur (7.34) and Harsaru Garhi (8.43) were the villages with the lowest and highest pH values, respectively. The correlation coefficient revealed that electrical conductivity (EC) of soil saturation extract was significantly and positively correlated with EC (0.962), Cl- (0.936) and Na+ (0.902) of groundwater used for irrigation.